PENGARUH RASIO LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB-SEKTOR INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - LUSIYANTI, RETNANING (Jurnal Akuntansi AKUNESA, 2014)
This study aims to determine the effect of liquidity and leverage ratios to value companies in the manufacturing sector companies sub-sectors of food and beverage industry are listed on the Stock Exchange in the year 2009-2011. In this study, the liquidity ratio was measured using the Current Ratio (CR), Acid Test Ratio (ATR). While the leverage ratio measured by Debt to Equity Ratio (DER) and Debt to Total Assets Ratio (DTA). The results showed that simultaneous liquidity and leverage ratios do not significantly influence the value of the company. Partially proved that the Acid Test Ratio (ATR), Debt to Equity Ratio (DER) and Debt to Total Assets Ratio (DTA) has a positive effect on firm value, but only the Acid Test Ratio (ATR), which gives them significant influence. While the Current Ratio (CR) has a negative but insignificant effect on firm value. Keywords : liquidity ratio, leverage ratio, firm value